Establishment of in vitro Calibration Curve for 60Co-γ-rays Induced Phospho-53BP1 Foci, Rapid Biodosimetry and Initial Triage, and Comparative Evaluations With γH2AX and Cytogenetic Assays - Chaurasia, Rajesh Kumar; Shirsath, Kapil B.; Desai, Utkarsha N.; Bhat, Nagesh N.; Sapra, B. K. (Frontiers in Public Health, 2022)
A rapid and reliable method for biodosimetry of populations exposed to ionizing radiation in the event of an incident or accident is crucial for initial triage and medical attention. DNA-double strand breaks (DSBs) are indicative of radiation exposure, and DSB-repair proteins (53BP1, γH2AX, ATM, etc.) are considered sensitive markers of DSB quantification. Phospho-53BP1 and γH2AX immunofluorescence technique serves as a sensitive, reliable, and reproducible tool for the detection and quantification of DSB-repair proteins, which can be used for biological dose estimations. In this study, dose-response curves were generated for 60Co-γ-rays induced phospho-53 Binding Protein 1 (phospho-53BP1) foci at 1, 2, 4, 8, 16, and 24 h, post-irradiation for a dose range of 0.05–4 Gy using fluorescence microscopy. Following ISO recommendations, minimum detection limits (MDLs) were estimated to be 16, 18, 25, 40, 50, and 75 mGy for dose-response curves generated at 1, 2, 4, 8, 16, and 24 h post-irradiation. Colocalization and correlation of phospho-53BP1 and γH2AX were also measured in irradiated peripheral blood lymphocytes (PBLs) to gain dual confirmation. Comparative evaluation of the established curve was made by γH2AX-immunofluorescence, dicentric chromosome assay (DCA), and reciprocal translocation (RT) assays by reconstructing the dose of 6 dose-blinded samples. Coefficients of respective in-house established dose-response curves were employed to reconstruct the blind doses. Estimated doses were within the variation of 4.124%. For lower doses (0.052 Gy), phospho-53BP1 and γH2AX assays gave closer estimates with the variation of −4.1 to + 9% in comparison to cytogenetic assays, where variations were −8.5 to 24%. For higher doses (3 and 4 Gy), both the cytogenetic and immunofluorescence (phospho-53BP1 and γH2AX), assays gave comparable close estimates, with −11.3 to + 14.3% and −10.3 to −13.7%, variations, respectively.